Analysis of energy, exergy and energy savings of a fire tube boiler - Hasanuzzaman, M.; Rahim, N.A.; Saidur, Rahman (2011)
Energy efficiency improvement as well as energy savings is the major concern in most of the development countries all over the world. In this study, the useful concept of energy and exergy utilization is analyzed to investigate the energy and exergy efficiency, energy and exergy losses and energy savings of boilers. The energy and exergy efficiencies of a combustion chamber and stream production chamber of the boiler have been analyzed as well. The exergy efficiency of the combustion chamber is found to be 49.6 . The energy and exergy efficiencies of the stream production chamber are found to be 55.4 and 34.6 respectively. The overall boiler energy and exergy efficiencies are found to be 60.3 and 19.9 respectively. It has been found that the combustion chamber is the major contributor for exergy destruction followed by stream production chamber of the boiler. By using heat recovery system, the savings will be 5278 L/year fuel that is about 7917 RM/year.